2020
DOI: 10.1177/0885328220920457
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of titanium manufactured through selective laser melting inhibited osteoclast differentiation through mitogen-activated protein kinase signaling pathway

Abstract: Selective laser melting used in manufacturing custom-made titanium implants becomes more popular. In view of the important role played by osteoclasts in peri-implant bone resorption and osseointegration, we modified selective laser melting-manufactured titanium surfaces using sandblasting/alkali-heating and sandblasting/acid-etching, and investigated their effect on osteoclast differentiation as well as their underlying mechanisms. The properties of the surfaces, including elements, roughness, wettabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Furthermore, our previous study reported that TNNs could inhibit osteoclast differentiation through the MAPK signaling pathway. 59 Therefore, TNN substrates could play a stronger role in inhibiting osteoclastogenesis than TNT substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our previous study reported that TNNs could inhibit osteoclast differentiation through the MAPK signaling pathway. 59 Therefore, TNN substrates could play a stronger role in inhibiting osteoclastogenesis than TNT substrates.…”
Section: Discussionmentioning
confidence: 99%
“…It is pointed out that SLM 316 L stainless steel prepared under high laser power conditions has good corrosion resistance and biocompatibility, while the SLM 316 L stainless steel prepared under low power conditions is poor and unstable. In 2020, Jiamin Yang et al [ 95 ] studied the differentiation of custom titanium implants with SLM on cell proliferation. The results show that powder‐based materials with more elements can be developed and used increasing the range of materials used for SLM.…”
Section: Powder‐based Methodsmentioning
confidence: 99%
“…This was indicated by cell culture studies of bone marrow-derived monocyte differentiation on implant surfaces cultured with osteoprogenitor cells. The rough surface provided local cues to adherent osteoprogenitors to direct osteoclast production (40,41). There are multimodal effects of enhanced surface topography that positively affect the accrual of bone at the titanium dental implant surface.…”
Section: The Superimposition Of Nanoscale Features On Micronrough Titanium Topography Increases the Expression Of Bonementioning
confidence: 99%